The effects of trans-fatty acids on TAG regulation in mice depend on dietary unsaturated fatty acids - Sain, Juliana (2016)
The aim of this study was to investigate the effects of trans-fatty acids (TFA) on liver and serum TAG regulation in mice fed diets containing different proportions of n-3, n-6 and n-9 unsaturated fatty acids (UFA) from olive (O), maize (C) or rapeseed (R) oils partially substituted or not with TFA (Ot, Ct and Rt, respectively). Male CF1 mice were fed (30 d) one of these diets. The effects of the partial substitution (1 %, w/w) of different UFA with TFA on the activity and expression of hepatic enzymes involved in lipogenesis and fatty acids oxidation were evaluated, as well as their transcription factor expressions. Some of the mechanisms involved in the serum TAG regulation, hepatic VLDL rich in TAG (VLDL-TAG) secretion rate and lipoprotein lipase (LPL) activity were assessed. In liver, TFA induced an increase in TAG content in the Ot and Rt groups, and this effect was associated with an imbalance between lipogenesis and β-oxidation. In the Ot group, exacerbated lipogenesis may be one of the mechanisms responsible for the liver steatosis induced by TFA, whereas in Rt it has been related to a decreased β-oxidation, compared with their respective controls. The enhanced hepatic VLDL-TAG secretion in the Ot and Rt groups was compensated with a differential removal of TAG by LPL enzyme in extrahepatic tissues, leading to unchanged serum TAG levels. In brief, the effects of low levels of TFA on liver and serum TAG regulation in mice depend on the dietary proportions of n-3, n-6 and n-9 UFA.